1978
DOI: 10.1099/0022-1317-38-2-329
|View full text |Cite
|
Sign up to set email alerts
|

In situ Degradation of the Protein Chain of Potato Virus X at the N- and C-termini

Abstract: SUMMARYThe amino acid composition, behaviour in SDS-polyacrylamide gel electrophoresis and electrophoretic patterns of cyanogen bromide peptides were studied for the protein subunits of different preparations of potato virus X (PVX). The results indicate that the protein subunits of PVX can be partially degraded in the intact virus at the N-terminus by reducing agent-dependent proteases in crude plant sap and by trypsin, and at the C-terminus by reducing agent-independent proteases occurring in some virus prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 17 publications
3
24
0
Order By: Relevance
“…The C terminus of the PVX capsid protein also seems to be located on the virus surface, since PAbs react with the 48 amino acid C-terminal CNBr fragment (Radavsky et al, 1988). Our results are in accord with those of Koenig et al (1978), which showed that N-and C-terminal portions of the capsid protein can be split off with proteases and that the resulting PVX particles can be distinguished by their reactions with PAbs (Koenig, 1972(Koenig, , 1978. Using rat MAbs to PVX, Koenig & Torrance (1986) clearly distinguished PVX particles with capsid proteins lacking N or C termini and found three antigenic determinants on the protein subunits of the B strain of PVX.…”
Section: Discussionsupporting
confidence: 80%
“…The C terminus of the PVX capsid protein also seems to be located on the virus surface, since PAbs react with the 48 amino acid C-terminal CNBr fragment (Radavsky et al, 1988). Our results are in accord with those of Koenig et al (1978), which showed that N-and C-terminal portions of the capsid protein can be split off with proteases and that the resulting PVX particles can be distinguished by their reactions with PAbs (Koenig, 1972(Koenig, , 1978. Using rat MAbs to PVX, Koenig & Torrance (1986) clearly distinguished PVX particles with capsid proteins lacking N or C termini and found three antigenic determinants on the protein subunits of the B strain of PVX.…”
Section: Discussionsupporting
confidence: 80%
“…Our results suggest that the quaternary structure of BNYVV may resemble that of other elongated plant viruses, such as tobacco mosaic virus (TMV) (Bloomer et al, 1978), potato virus X (PVX) (Koenig et al, 1978;Sawyer et al, 1987) and potyviruses (Allison et al, t985;Shukla et al, 1988), in that the C terminus of the coat protein is exposed. The C terminus of the BNYVV coat protein apparently carries the continuous epitope 4 which seems to be strongly immunogenic.…”
Section: Resultsmentioning
confidence: 91%
“…Thus the 59K protein may contain the sequence between amino acid 838 and the end of the 150K polyprotein, and the 57K protein may arise from it by the loss of the C-terminal amino acids. It is known that proteases can remove amino acids from the C termini of the coat proteins of tobacco mosaic virus (Harris & Knight, 1952), potato virus X (Koenig et al, 1978) and potyviruses (Shukla et al, 1988). Presumably, as with these viruses, the C-terminal amino acids of TBRV coat protein protrude from the virus particle surface and can be removed without disrupting the virion.…”
Section: Discussionmentioning
confidence: 99%